Identification of the Aerosol Types over Athens, Greece: The Influence of Air-Mass Transport - D. G. Kaskaoutis; P. G. Kosmopoulos; H. D. Kambezidis; P. T. Nastos (Advances in Meteorology)
Aerosol optical depth at 550 nm (AOD550) and fine-mode (FM) fraction data from Terra-MODIS were obtained over the Greater Athens Area covering the period February 2000–December 2005. Based on both AOD550 and FM values three main aerosol types have been discriminated corresponding to urban/industrial aerosols, clean maritime conditions, and coarse-mode, probably desert dust, particles. Five main sectors were identified for the classification of the air-mass trajectories, which were further used in the analysis of the (AOD550 and FM data for the three aerosol types). The HYSPLIT model was used to compute back trajectories at three altitudes to investigate the relation between AOD550-FM and wind sector depending on the altitude. The accumulation of local pollution is favored in spring and corresponds to air masses at lower altitudes originating from Eastern Europe and the Balkan. Clean maritime conditions are rare over Athens, limited in the winter season and associated with air masses from the Western or Northwestern sector. The coarse-mode particles origin seems to be more complicated proportionally to the season. Thus, in summer the Northern sector dominates, while in the other seasons, and especially in spring, the air masses belong to the Southern sector enriched with Saharan dust aerosols.